If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + y + 2 = -16 Reorder the terms: 2 + y + y = -16 Combine like terms: y + y = 2y 2 + 2y = -16 Solving 2 + 2y = -16 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 2y = -16 + -2 Combine like terms: 2 + -2 = 0 0 + 2y = -16 + -2 2y = -16 + -2 Combine like terms: -16 + -2 = -18 2y = -18 Divide each side by '2'. y = -9 Simplifying y = -9
| 14=7x+5 | | n+3+5=-6 | | 180=37x-13 | | 7+2/3x=13 | | 4x+21x=-119 | | 63=n+28 | | 5x-2-3-x+2=9 | | x(x+9)=x^2+15x+12 | | 25-15+14= | | 6x-7=7+4x | | 9m^3-3m^2p^2-3mp+p^3= | | v-13=-7(4v+6) | | 5(r-1)=2(-3-4)-6 | | -7+8.5=14.2 | | 17x^2+576=x(x+118)-46x | | .5x-3=1.15x+4 | | 17x-9=15x+3 | | 6n-5+6=-23 | | -8x^6+1= | | 5-(t+6)=-1+2(t-3) | | 3s^2-8s-11=0 | | -2n-29=3(1-6n) | | 5(2*x-3)=15 | | .75x=190 | | 5(1-7b)=2b-32 | | 3(-5a+7)=111 | | 5x^2+x^3=6 | | (5k^4+5)-(4k^3-2k^4)= | | 3(x-7)+2x=5(x+4)-41 | | 3(x-1)=-(x-5) | | 22x+22=118 | | -23=-2*a-10+a |